Spirit possession and witchcraft in modern Sudan - Μακρής Γεράσιμος (The Greek Review of Social Research, 2013)
I present critically zar tumbura, a Sudanese spirit possession cult practised mainly by black Africans of slave descent. Following tumbura’s historical transformations in an environment dominated by Arab-Islamic versions of Sudanese identity, I show how cult membership allows the cult’s subaltern devotees to construct a positive self-identity as “true” Muslims and “real” owners of the Arab dominated Sudan. Through the careful study of rich ethnographic data, the article functions as a window for the analysis of wider socio-cultural transformations in a society where the Arab and African worlds meet within a shared universe of Islamic hybrids during a period of violent neoliberal deregulation under the heavy hand of an Arab Islamist dictatorship.